Comparative study of E-pharmacy & Unorganized pharmacy in West Bengal - Bose, Dibakar; Kar, Saikat Kumar; Kumar, Chandan; Banerjee, Kaushik (International Journal of Psychosocial Rehabilitation, 2020)
Pharmacy business is not only a business for profit earning it is also for the welfare of humanity. Generally, medicine is purchase through physical medical stores but in the last few years, some online e-pharmacy came in the market and growing day by day. In India, there are lots of controversies regarding the selling of medicine online. Medicine is something that human need for alive in this world and pharma industry is growing day by day so no one willing to welcome new competitor in the market. All India Chemist and Druggist Association (AICDA) which is the union body of unorganized pharmacy on strike for 4 times in the last 2 years due to E-pharmacy business in India. The purpose of the strike was not up to the mark we find after doing this survey. Selling some restricted medicine (antibiotic, painkiller, and others) without prescription is also done in most of the counter medical store. Most of the unorganized counter not providing bill also to the customers. Validation of prescription is not possible in India until and unless we adopt some kind of technology for that. E-pharmacy has come up with lots of challenge like strike by AICDA, Delhi & Madras High Court order but survey revealed that 95.63% interviewee willing to buy medicine from online in future. Purpose of the study is to find the challenges & opportunity of e-pharmacy &unorganized pharmacy in West Bengal as well as customer psychology about e-pharmacy &unorganized pharmacy.